Pengaruh Kegiatan Ekstrakurikuler Paduan Suara Terhadap Hasil Belajar Seni Budaya (Bernyanyi Lagu Daerah) Di SMP Negeri 10 Padang - Diovani Rahardi Thursdila; Esy Maestro (FBS Universitas Negeri Padang, 2020)
This study aims to determine whether choir extracurricular activities affect student learning outcomes. This research is a quantitative research with correlation method. Theories used are about extracurricular, choir, learning and instruction, learning outcomes, andCulture and Arts.The data supporting this study sourced from primary data and secondary data. The results show that there is a significant relationship between extracurricular activities and the learning outcomesof singing folk songs. Based on the calculation of simple correlation test, it shows that r count> r table (0.853> 0.831). Thus, it can be concluded that the relationship is positive and can be continued with a significant test. Significant test is sought by using the t test. The resultgot istcount>ttable (7.004> 1.907). This value gives a conclusion that there is a positive and significant relationship between the choir extracurricular activities (X) on the learning outcomes of arts and culture (Y) at SMP N 10 Padang.